Information Seeking Behaviors in the Library and on the Internet Consisting of 10-11 age group’s children Grade 4 Students - Esmeray Karataş Ateş (Türk Kütüphaneciliği)
This is a qualitative study, carried out with the aim to analyze the behavior of children in regard to information seeking behaviors in libraries and on the internet. 115 children of an age group between 10-11 years have been selected among Grade 4 students in order to execute this research. 115 students participating in the study were asked a total of 16 questions, of which 14 were closed-ended and 2 open- ended. Responses to open-ended questions were analyzed by using the content analysis technique. Upon the data analysis result; the following factors were determined: children’s information seek objectives and methods in the library and on the internet, information resource priority, information seek friendliness, methods of information seek in books and on the internet, search engine preferences, forms of usage and evaluation of the information obtained and difficulties encountered when seeking for information in printed resources and on the internet. The findings are as follows: Children require guidance when searching for information in the library, they use internet instead of library and they use search engine instead of library catalogue, they seek for any kind of information both in the library and on the internet, when seeking for information they first seek in books, the easiest way for them to look for information is to take a look to the internet, when they seek for information in books, they most frequently take a look in the content section, when they seek for information on the internet, they most frequently take a look in the first page the site has provided, when they seek for information on the internet, they most frequently use Google search engine, they are first taking notes about the information obtained in the library and on the internet, they doubt the accuracy of the information they obtained on the internet and they have difficulties in finding printed and electronic information appropriate for their comprehension level.